Are Hooded seals (Cystophora cristata) endowed with mechanisms for non-shivering thermogenesis within the skeletal muscle? - Chiu, Matthew (UiT Norges arktiske universitet, 2022)
Hooded seals (Cystophora cristata) are marine mammals and are characterised as an “Arctic seal” species due to their close association to the pack ice. Their relationship with the ice and water creates challenges in maintaining an internal body temperature of ~37°C. In homeothermic animals, like the hooded seal, shivering is used for thermogenesis, however this can rapidly fatigue skeletal muscle. Other mechanisms of thermogenesis have been found which do not employ the use of shivering thermogenesis and are termed non-shivering thermogenesis (NST) mechanisms. A common area of NST study is the thermogenic mechanism found in brown adipose tissue (BAT). The presence of BAT in mammals is common, particularly in the neonatal life stages where surface area to volume ratio is high and is noticeably present in other seal species e.g. harp seals, which share the same distribution and environmental hardships as hooded seals. However, the presence of BAT has not been reported in hooded seals. Studies in other species have shown that in the absence of BAT, skeletal muscle tissue can be utilised in a non-shivering mechanism using an interaction between Sarcolipin (Sln) and Ca2+ ATPase (SERCA) transport protein that produces futile cycling of Ca2+, as well as through a decreased efficiency in mitochondrial processes known as mitochondrial proton LEAK. Within this study I set out to find whether hooded seals utilise these skeletal muscle based, non-shivering thermogenesis mechanisms and whether those mechanisms are most likely to be found in the neonatal life stages compared to later life stages. In silico DNA sequence comparisons of Sln, and the SERCA isoforms, SERCA1a and SERCA2a across 10 mammals including marine mammals from the suborder Pinnipedia revealed that these proteins were highly conserved providing proof of principle that a Sln-SERCA NST mechanism could exist. To identify these proteins in hooded seals, western blotting of skeletal muscle samples taken from M. longissimus dorsi (M. long) and Psoas major (P. ...